2021
DOI: 10.3389/fphar.2021.650816
|View full text |Cite
|
Sign up to set email alerts
|

Fuzhenghefuzhiyang Formula (FZHFZY) Improves Epidermal Differentiation via Suppression of the Akt/mTORC1/S6K1 Signalling Pathway in Psoriatic Models

Abstract: Psoriasis is a chronic proliferative skin disorder characterised by abnormal epidermal differentiation. The Fuzhenghefuzhiyang (FZHFZY) formula created by Chuanjian Lu, a master of Chinese medicine in dermatology, has been external used in the Guangdong Provincial Hospital of Chinese Medicine for the treatment of psoriasis, but its mechanisms of action against psoriasis remain poorly understood. This study involved an exploration of the effects of FZHFZY on epidermal differentiation and its underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Studies have reported hyperactivity of AKT/mTOR and its downstream molecular target ribosomal protein S6 kinase 1 (S6K1) in the skin lesions of patients with psoriasis [49,50], and the highly active PI3K/AKT/mTOR pathway can lead to the abnormal differentiation of keratinocytes, which is generally recognized as a main pathological feature of psoriasis [16,46]. Inactivation of PI3K/AKT signaling provides a novel approach in psoriasis management [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported hyperactivity of AKT/mTOR and its downstream molecular target ribosomal protein S6 kinase 1 (S6K1) in the skin lesions of patients with psoriasis [49,50], and the highly active PI3K/AKT/mTOR pathway can lead to the abnormal differentiation of keratinocytes, which is generally recognized as a main pathological feature of psoriasis [16,46]. Inactivation of PI3K/AKT signaling provides a novel approach in psoriasis management [61].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic epidermal hyperplasia in psoriatic lesions is due to keratinocytes proliferation and main events of the immune response expressed by overactivation of PI3K/AKT/mTORC1 and STAT3 signaling cascades [46,47]. The apoptosis induction was reported as a key mechanism for regression of psoriatic hyperplasia with conventional UVA and methotrexate therapy [47,48].…”
Section: Effect Of H Procumbens Extract and Pure Ver And Leu On Expre...mentioning
confidence: 99%
See 1 more Smart Citation
“…The primer sequences used in this study are listed in Table 1 . The relative mRNA quantities were determined by the 2 −ΔΔCT method ( Lu et al, 2021 ), and further normalized to that of the GAPDH housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) has great advantages and broad prospects in the treatment of psoriasis, and has accumulated rich treatment experience over a long time ( Yu et al, 2013 ; Zhang et al, 2014 ; Zhang et al, 2016 ; Yu et al, 2017 ). PSORI-CM02 and FZHFZY has been used for decades to treat blood stasis and blood dryness syndromes of psoriasis vulgaris at the Guangdong Provincial Hospital of Chinese Medicine ( Lu et al, 2019 ; Lu et al, 2021a ; Lu et al, 2021b ). PSORI-CM02 consists of Rhizoma Curcumae ( Curcuma longa L.), Radix Paeoniae rubra ( Paeonia lactiflora Pall.…”
Section: Introductionmentioning
confidence: 99%